2015
DOI: 10.1016/j.annepidem.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Low tobacco-related cancer incidence in offspring of long-lived siblings: a comparison with Danish national cancer registry data

Abstract: Purpose Familial clustering of longevity is well documented and includes both genetic and other familial factors, but the specific underlying mechanisms are largely unknown. We examined whether low incidence of specific cancers is a mechanism for familial clustering of longevity. Methods The study-population of individuals from longevity-enriched families consisted of 3267 offspring from 610 Danish long-lived families defined by two siblings attaining an age of 90+. The offspring of the long-lived siblings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…This minimizes loss to follow‐up and healthy participant bias at the expense of no available survey data on behavior. Using the Danish Cancer Registry, we have demonstrated low occurrence of cancers in the offspring of long‐lived siblings (Pedersen et al, 2015). We confirmed these findings using the Danish Patient Registry, and we extended the analyses to the grandchildren who, despite being followed only up to age 49, also showed lower cancer rates compared to controls, most pronounced for tobacco‐related cancers, although only borderline statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This minimizes loss to follow‐up and healthy participant bias at the expense of no available survey data on behavior. Using the Danish Cancer Registry, we have demonstrated low occurrence of cancers in the offspring of long‐lived siblings (Pedersen et al, 2015). We confirmed these findings using the Danish Patient Registry, and we extended the analyses to the grandchildren who, despite being followed only up to age 49, also showed lower cancer rates compared to controls, most pronounced for tobacco‐related cancers, although only borderline statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The lower rates of tobacco‐related cancers in offspring and grandchildren could be due to both lower smoking frequency and/or higher biological resilience to the carcinogenic effects of tobacco in individuals with a familial history of longevity. Smoking habits in offspring were available for the subset of families in our study who also participated in the Long Life Family Study , and Pedersen et al (2015) showed that the prevalence of smokers in the offspring was 24% lower than that predicted from age‐ and sex‐specific smoking prevalence in the Danish population (Den Nationale & Sundhedsprofil, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a 2015 population-based study that included the offspring of long-lived siblings (surviving to at least 90 years of age) the offspring had one third of the expected lung cancer incidence 8 . As the incidence of lung cancer is strongly correlated with lifestyle, these findings suggest that a healthy lifestyle might be a main driver for the familial clustering of exceptional good health.…”
mentioning
confidence: 99%